PENGARUH PEMAKAI DAN KONFLIK PEMAKAI TERHADAP KUALITAS SISTEM INFORMASI AKUNTANSI DENGAN LIMA VARIABEL MODERATING DI SKPD PEKANBARU - Kusumaningdiah Retno Setiorini (JESI (Jurnal Ekonomi Syariah Indonesia), 2015)
Abstract The purpose of this study was to test the inﬂ uence of users and user conﬂ ict on the quality of accounting information systems with superior support, user communications developer, the complexity of the task, the complexity of the system, the user experience as a variable moderating. The method used survey method with processed primary data obtained from the questionnaire. The population in this study was 98 SKPD Pekanbaru which has a function as a task of ﬁ nancial matters relating to the quality of accounting information systems with the number of samples that can be analyzed as much data as 78 respondents. The sampling technique used purposive sampling. Test data validation and reliability of respondent data using Pearson product moment and Cronbach’s alpha. Data were analyzed using Moderated Regression Analysis (MRA). The results showed (1) Effect of users positive effect on the quality of accounting information systems. (2) Conﬂ ict users will not negatively affect the quality of accounting information system. (3) The inﬂ uence of supervisor support moderated wearer no positive effect on the quality of accounting information systems. (4) The effect of the user moderated user communications developer is not a positive inﬂ uence on the quality of accounting information systems. (5) Effect of users moderated complexity of the task is not a positive inﬂ uence on the quality of accounting information systems. (6) The effect of the user moderated system complexity is not a positive inﬂ uence on the quality of accounting information systems. (7) Effect of the wearer moderated user experience no positive effect on the quality of accounting information systems. (8) Conﬂ ict wearer superior failed to support moderated negative effect on the quality of accounting information systems. (9) Conﬂ ict wearer user communication moderated the developer is not a negative effect on the quality of accounting information systems. (10) The conﬂ ict wearer moderated complexity of the task is not a negative effect on the quality of accounting information systems. (11) Conﬂ icts user moderated system complexity is not a negative effect on the quality of accounting information systems. (12) Conﬂ icts wearer moderated user experience a negative effect on the quality of accounting information system. Keywords: inﬂ uence of users, user conﬂ ict, supervisor support, user communications developer, the complexity of the task, the complexity of the system, the user experience.